On the bound-state spectrum of a nonrelativistic particle in the background of a short-ranged linear potential - Castro, L. B. [UNESP]; de Castro, A. S. [UNESP] (My University, 2010)
The nonrelativistic problem of a particle immersed in a triangular potential well, set forth by N. A. Rao and B. A. Kagali, is revised. It is shown that these researchers misunderstood the full meaning of the potential and obtained a wrong quantization condition. By exploring the space inversion symmetry, this work presents the correct solution to this problem with potential applications in electronics in a simple and transparent way. © Electronic Journal of Theoretical Physics. All rights reserved.
Keywords: Airy functions; Linear potential; Triangular potential